Canakinumab for the treatment of adult-onset Still's disease. (1st February 2020) - Sfriso, Paolo; Bindoli, Sara; Doria, Andrea; Feist, Eugen; Galozzi, Paola
ABSTRACT: Introduction : Adult-onset Still's disease (AOSD) is a rare multisystem autoinflammatory disorder of unknown etiology, with clinical and biological similarities with the juvenile form (sJIA). The pivotal role of interleukin (IL)-1 gives rise to the use of IL-1 inhibitors in treating resistant cases. Areas covered : This review focuses on canakinumab, a fully human anti-IL-1β antibody, as treatment for AOSD. The data obtained from case reports and case series on AOSD and two double-blind, randomized, placebo-controlled Phase III trial on sJIA are analyzed. Efficacy and safety profiles of canakinumab are discussed. Expert opinion : There is no unanimous consensus on how to treat with IL-1 inhibitors. Many reviews have focused primarily on anakinra, but the accumulating data for canakinumab have emerged. The choice of treatment is a relevant issue for patients and the national health services. The available data for canakinumab indicate that this drug in AOSD patients is effective and well tolerated.